Investigating the Effectiveness of Creating Shared Value and Corporate Social Responsibility as Differentiation and Sustainability Strategies for Corporations in Malaysia - Mohamed, Mohamed Salum (2014)
This research provides the perspective on Creating Shared Value (CVS) as an effective differentiation and sustainability strategy for corporations. The main purpose of this research is to investigate an effectiveness of Creating Shared Value (CSV) and Corporate Social Responsibility (CSR) as differentiation and sustainability strategies for Corporation in Malaysia. Five semi structured in-depth interviews which were conducted with the Executive Directors, Marketing and CSR Managers who are working in the Multinational Corporation which are practicing CSV within their operations. The data were analyzed as template analysis with two main themes (i) Differentiations and (ii) Sustainability, and fifteen sub themes: six themes under differentiation and nine themes under sustainability. Validity and reliability of the findings for this research were conducted to show the degree of significance of the different themes of effective approach which can integrate business and society in terms of differentiation and sustainability. The findings of the research show that CSV approach is an effective approach to be implemented in the corporations in Malaysia in comparison to CSR. This is because CSV is about enhancing the economics level of the corporation by addressing the society issues. The results of this thesis have contributed into the world of knowledge and practice. Limitations are discussed at the end for the purpose of exploring the possibilities for future research. There are recommendations especially for the particular professionals and Government.